PERSEPSI PEMILIH TENTANG KAMPANYE KOTAK KOSONG : KASUS BERITA TIRTO.ID PADA PEMILU 2024 - Nazwa Putri Septiani; Chika Rahma Aulia; Rakha Ahmad Ramadhan; Muhammad Haikal; Pia Khoirotun Nisa (CV. ALIM'SPUBLISHING, 2025)
shows that there are segments of society who feel they are not represented by the existing candidates. The high number of blank ballots indicates that many voters are dissatisfied with the choices available, so they choose not to vote for a candidate at all. This is a clear signal for political parties and candidates to listen more to the voice of the people. The implementation of campaigns is regulated in National Security Council Decree Number 11640 dated 2 May 1955. This decision does not determine the period for the campaign, but only states that the campaign ends the day before the voting. In Indonesia, the